An Impact of Artificial Intelligence Based on Digital Marketing with Special Reference to Tirunelveli City (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
Artificial intelligence is a technology that allows computers or machines to think like humans and accomplish tasks that are similar to those performed by the human brain. Artificial Intelligence and technological advancements are now being applied in practically in all facets of life. It has been used in conjunction with digital marketing to help firms reach out to customer at the proper time. “Marketers have the ability to process large amounts of data and meet client expectations. It has been that AI has been used to ensure customer satisfaction”. The use of the internet is growing in India, which opens up new commercial options. Artificial Intelligence (AI) in the modern era is a broad field that employs advanced techniques to derive viewpoints from vast volumes of data. The basic idea behind AI is to teach robots to practice, resolve problem that is faced on a regular basis. The AI is enabled in supporting the management to create and monitor various digital content, assist in understanding the overall needs of the customers and enable in providing the necessary information to the management for taking key decisions. The AI helps the marketers to create distinct advantage and enable in providing better products and services to the customers.